Micro-Credential in Integrated and Sustainable Urban Farming: Urban Farming and AgroEntrepreneurship - Rosman, Romzie; Puat Nelson, Sherliza; Md Dahlal, Norazilawati (2021)
The module intends to increase learners’ knowledge of the concept of urban farming and agro-entrepreneurship. The learners also will be guided on the fundamental of bookkeeping and accounting for small agro-entrepreneur.